Emotional intelligence training for pre-service primary school teachers: a mixed methods research - Özdemir Cihan, Meryem; Dilekmen, Mücahit (Frontiers in Psychology, 2024)
Introduction: This research devises a training program for developing emotional intelligence focused on social and emotional learning and integrates it into teaching to improve pre-service teachers' emotional intelligence.The study used a embedded mixed design. The quantitative dimension of the study used a controlled quasi-experimental design with pre-test/post-test, and the qualitative dimension used an evaluative case study design. The study was conducted with 73 prospective primary school teachers studying at the faculty of education of a Turkish state university. The study group was formed using purposive random sampling. The sample for the quantitative dimension was composed using probability random sampling, whereas the sample for the qualitative dimension was composed using purposive sampling. The program was administered to the experimental group for 10 weeks. Quantitative data were obtained using the Bar-On EQ-i, and qualitative data were obtained using a semi-structured interview questionnaire and participant diaries. Quantitative data were analyzed using normality analysis and one-factor analysis of covariance, whereas qualitative data were analyzed using descriptive and content analysis.The results found the developed training program to be an effective approach to improve emotional intelligence among pre-service teachers. Moreover, data obtained from documentary sources and focus group interviews during and after the application of the program confirmed and adequately explained the quantitative results.In line with the purpose of the study, the findings obtained from the quantitative part of the study showed that the implementation of the training program for the development of emotional intelligence focused on SEL was an effective approach in increasing the emotional intelligence levels of the pre-service teachers in the experimental group. Similar research results also support that preservice teachers' emotional intelligence can be improved with additional intervention practices without affecting their curriculum.